Obesity- An Adverse Factor in Reproductive Age - Ansari, Saba (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
Obesity is a global health risk. Demography of the world population has witnessed a dramatic change concerning body weight. The Increase in the prevalence of obesity is prevailing in the world nations in general and in industrialized nations in particular. There is a growing body of evidence showing reproductive age as a landmark for important contributor to this epidemic of obesity. Obesity prevention and management is a key health issue for the woman of reproductive age.
Keywords: Body weight